Effectiveness of vibratory added mixing concrete with heating-grinding recycled coarse aggregate. Issue 1 (September 2021) - Kencanawati, N N; Hariyadi, H; Akmaluddin, A; Karyawan, I D M A; Mahmud, F; Saputro, P N
Abstract: Concrete is a building material that is widely used in the construction industry. With the increasing need for concrete, the demand for constituent materials will increase. To reduce dependence on natural materials, the recycling process of the concrete waste has been encouraged recently. This study applied a heating and grinding method of waste concrete to obtain higher quality recycled coarse aggregate. The addition of vibrations in the mixing process is aimed to enhance the recycled concrete compressive strength. To produce recycled coarse aggregate, the concrete waste was heated to a temperature of 100°C for 24 hours followed by a grinding process using a Los Angeles machine for 600 cycles. Additional vibrations for 30, 60, and 90 were applied in a concrete mixer during the mixing process. Conventional concrete with normal aggregate and no additional vibration during mixing was also provided for comparison. According to the experimental results, the quality of natural coarse aggregate and the recycled one using heating and grinding methods is not much different. Compressive strength of recycled aggregate concrete with vibrations of 30, 60, and 90 seconds increases 21.1%, 22.1%, and 22.6% sequentially correlated to normal concrete. Recycled concrete using heating and grinding methods with the addition of vibration during the mixing process is effective to be used as an alternative to normal coarse aggregate.